2014
DOI: 10.1186/s12935-014-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells promote carcinoma growth and lymph node metastasis when co-injected with esophageal carcinoma cells in nude mice

Abstract: BackgroundHuman umbilical cord blood derived-mesenchymal stem cells (hUCMSCs) offer an attractive alternative to bone marrow-derived MSCs (BMMSCs) for cell-based therapy as it is a less invasive source of biological material. However, limited studies have been conducted with hUCMSCs as compared to BMMSCs. The present study was conducted to evaluate the effects of hUCMSCs in esophageal carcinoma (EC).MethodshUCMSCs together with EC cells were transplanted subcutaneously into BALB/c nude mice to observe the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Its downregulation together with Bcl-xL, MMP-2, MMP-9, and cyclin D1 provides a pathway through which proliferation is inhibited and apoptosis is induced. It has been shown that human umbilical cord mesenchymal stromal cells promote carcinoma growth when coinjected with esophageal carcinoma cells in nude mice [ 68 , 69 ]. Their results differ from those reported in this in vitro study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its downregulation together with Bcl-xL, MMP-2, MMP-9, and cyclin D1 provides a pathway through which proliferation is inhibited and apoptosis is induced. It has been shown that human umbilical cord mesenchymal stromal cells promote carcinoma growth when coinjected with esophageal carcinoma cells in nude mice [ 68 , 69 ]. Their results differ from those reported in this in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be that cancer cells secrete many chemokines such as IL6 and IL8 and can stimulate migration in cancer cells; thus, the decreased IL6 and IL8 expression observed in this study (data not shown) suggest that it is associated with the decrease in cancer survival genes such as BCL-2, BCL-XL, MMP-2, and MMP-9 . MMP-2 and MMP-9 are the two most important proteins associated with tumour cell invasion and metastasis [ 68 , 69 ]. We observed in this study that both MMP-2 and MMP-9 protein levels and activity are downregulated in the presence of WJ-MSCs and fd-ECM, clearly showing that both MSCs and fd-ECM have an effect on “cancer survival” genes.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we must undertake far-reaching precautions and moderate enthusiasm in the implementation of WJ-MSC as anticancer therapy, since reports of tumor supporting function were recently published in regard to esophageal carcinoma [ 79 ] and renal cancer [ 80 ].…”
Section: More Differences Between Adult and Wharton's Jelly Derivementioning
confidence: 99%
“…An increase in metastatic characteristics was seen in MDA-MB-231 breast cancer cells in an orthotopic mouse model [20], esophageal cell lines TE-1 and Eca109 in vitro and in vivo [14] and A549 lung cancer cells [21].…”
Section: The Role Of Mscs In Cancer Development and Progressionmentioning
confidence: 99%
“…MSCs were shown to increase initiation and growth rates of a variety of tumour types including gastric cancer [13], esophageal cancer [14] and MCF7/Ras breast cancer [4], generally through the secretion of anti-apoptotic and pro-proliferative cytokines, for example via production of CCL5 (RANTES) and interleukin-6 in breast cancer models ( [4,15] and see Zimmerlin et al [16] for a more complete list of cytokines). It is also possible that cytokines found to be produced by MSCs in non-cancerous situations, for example, in wound healing, hematopoiesis and arteriogenesis, might also be secreted in cancer [17][18][19].…”
Section: The Role Of Mscs In Cancer Development and Progressionmentioning
confidence: 99%